Tinjauan Yuridis Tindak Pidana Kebiri dalam Perspektif Hak Asasi Manusia - I Gede Fajar Manggala; Anak Agung Sagung Laksmi Dewi; Luh Putu Suryani (Warmadewa Press, 2021)
The actions of a person who does something that is detrimental to others, for example torture, harassment, murder to result in death are required to be accountable for their actions. This study aims to determine the regulation of castration from a human rights perspective and to determine the sanction of castration from a human rights perspective. The method used is normative legal research which is carried out by recording and studying based on legal materials. The results of the study show that the punishment for castration is a maximum of 15 years and a maximum fine of five billion rupiah is a government action in an effort to eliminate discriminatory actions against a person's human rights. The government's decision regarding the sanctions given to perpetrators of the criminal act of castration is considered excessive by the National Human Rights Commission because it violates human rights and is too serious for the perpetrators but is still supported in order to eliminate acts of abuse against children as the nation's next generation.